Evidence-based medicine. Chronic Chagas disease grave, with ventricular aneurysm and their treatment - Lazo Salazar, Ramón (Revista Universidad de Guayaquil, 2010)
A patient with severe chronic Chagas disease with ventricular aneurysm programmed to cardiac surgery is reported. New cardiovascular evaluation suggested to start with Fight Chagas specific medical treatment. General check up previously Chagas therapy was carried out. A remarkable health improvement was registered after specific treatment. Patient did not come back to follow up control during next four years. Therefore when I was designed for teaching human Trypanosomosis complications in Tropical Medicine Mastery post graduated course organized by University Studies considered important to include this case, so I called to the patient pointing out control needing and I suggested to the students to travel to St. Lucia patient home town to insist her to come. Thus her participation was really convinience, since it revealed the evolution and the medicine based in evidence asserts. Specific tests and physical examination showed a remarkable recovery, despite ventricular aneurysm persistance. It was considered a good clinical prognosis to register a 60% ejection fraction, since drug action was undoubtedly revealing a Fight Chagas treatment success.
Keywords: Evidence-based medicine; Clinical experience; Chronic Chagas disease; Ventricular aneurysm